Mediators of Inflammation and Angiogenesis in Chronic Spontaneous Urticaria: Are They Potential Biomarkers of the Disease? - Ilaria Puxeddu; Federico Pratesi; Domenico Ribatti; Paola Migliorini (Hindawi Limited, 2017)
In chronic spontaneous urticaria (CSU), different pathophysiological mechanisms, potentially responsible for the development of the disease, have been recently described. It is likely that the activation of skin mast cells with consequent release of histamine and other proinflammatory mediators is responsible for vasodilation in the lesional skin of CSU. However, the underlying causes of mast cell activation in the disease are largely unknown and remain to be identified. Thus, in this review, we discuss new insights in the pathogenesis of CSU, focusing on inflammation and angiogenesis. The understanding of these mechanisms will enable the identification of biomarkers useful for the diagnosis, follow-up, and management of CSU and will allow the development of novel, more specific, and patient-tailored therapies.